A COMPARATIVE STUDY OF TYMPANOPLASTY WITH OR WITHOUT MASTOIDECTOMY IN TUBOTYMPANIC TYPE OF CHRONIC SUPPURATIVE OTITIS MEDIA - Dr. Neeraj Murkey; Dr. Srushti Agham; Dr. Syed Zafir Waqui; Dr. Prajakta Mowale; Dr. Manish H. Rathi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background- Chronic suppurative otitis media (CSOM) ranks among the prevalent ear disorder in developing nations. The absence of aerating mastoidectomy during the initial tympanoplasty is identified as a potential cause of failure in individuals with chronic non-cholesteatomatous otitis media. Consequently, the combination of cortical mastoidectomy with tympanoplasty has been consistently regarded as the preferred surgical intervention. Our research aims to investigate the efficacy of tympanoplasty, both with and without cortical mastoidectomy.Method- The current research was performed in the department of ENT outpatient at a tertiary care hospital in Maharashtra, India. The study included 50 patients of both genders who attended the outpatient clinic in the department of ENT. Their chief complaint was a discharging ear with decreased hearing during the two-year study period. Out of the 50 individuals who had surgical treatment, tympanoplasty with mastoidectomy was performed in 25 cases, while tympanoplasty without mastoidectomy was done in the remaining 25 cases.Result: In the current study, we found a higher prevalence of chronic suppurative otitis media in females compared to males. In x-ray bilateral mastoids Schuller’s view, 26 individuals (54%) had sclerotic mastoids and 24 individuals (46%) had pneumatic mastoids. Clinical improvement, graft uptake, and postoperative hearing improvement were alike in both groupsConclusions: CSOM seems to be more prevalent among females. The enhancement in hearing after undergoing either tympanoplasty alone or combined tympanoplasty with mastoidectomy demonstrated similar outcomes in both cohorts. It was observed that incorporating mastoidectomy into tympanoplasty did not yield additional advantages in terms of improvement in hearing